Liberation in a Religiously Plural World: The Problem of Normative Christological Claims in Latin American Liberation Theology - McCarthy, Kate (Toronto journal of theology, 1994)
In efforts to define key features of Latin American liberation theology, orthopraxis is often given precedence over orthodoxy, that is, right action over right belief. This is useful shorthand for recent Latin American theological efforts, and yet it leaves unanswered an important question. Once the truth claims of traditional belief formulas are removed from the theological throne, what is to be done with them? Such claims are certainly not absent from the work of liberation theologians, and yet their status remains relatively unexamined. I will consider the question here by examining in the works of Gustavo Gutierrez and Jose Miguez Bonino the particular claim to the normative status of Christian revelation in light of the world's religious pluralism. Should such claims be accepted? Should they be reinterpreted in terms more agreeable to contemporary world views? Should they be jettisoned? In any case, it appears clear that they cannot remain impervious to critical examination. Such examination exposes both the liabilities of traditional christological formulas in liberation theology and the resources that theology offers for reinterpreting these claims in the service of both the liberation project itself and the wider effort to make theological sense in a pluralistic world.